Collagen Dynamics During the Process of Osteocyte Embedding and Mineralization - Shiflett, Lora A.; Tiede-Lewis, LeAnn M.; Xie, Yixia; Lu, Yongbo; Ray, Eleanor C.; Dallas, Sarah L. (Frontiers in Cell and Developmental Biology, 2019)
Bone formation, remodeling and repair are dynamic processes, involving cell migration, ECM assembly, osteocyte embedding, and bone resorption. Using live-cell imaging, we previously showed that osteoblast assembly of the ECM proteins fibronectin and collagen is highly dynamic and is integrated with cell motility. Additionally, osteoblast-to-osteocyte transition involved arrest of cell motility, followed by dendrite extension and retraction that may regulate positioning of embedding osteocytes. To further understand how osteocytes differentiate and embed in collagen, mice were generated that co-expressed GFPtopaz-tagged collagen with a Dmp1-Cre-inducible tdTomato reporter targeted to preosteocytes/osteocytes. Dual live-cell imaging of collagen and osteocyte dynamics in mineralizing primary calvarial cell cultures showed that Dmp1-Cre/tdTomato turned on in early bone nodule forming regions, demarcated by foci of concentrated GFP-collagen bundles that appeared structurally distinct from the surrounding collagen. Dmp1-Cre/tdTomato-positive cells were post-mitotic and were continuously induced throughout the 2-week timecourse, whereas the majority of collagen was assembled by day 7. GFP-collagen fibrils showed global (tissue-level) motions, suggesting coordinated cell layer movement, and local fibril motions mediated by cell-generated forces. Condensation of collagen fibril networks occurred within bone nodules prior to mineralization. Intravital imaging confirmed a similar structural appearance of GFP-collagen in calvarial bone, with analogous global motions of mineralizing areas adjacent to sutures. In early (unmineralized) calvarial cell cultures, Dmp1-Cre/tdTomato-positive cells were motile (mean velocity 4.8µm/h), moving freely in and around the forming bone nodule, with a small number of these cells embedded in collagen, constraining their motion. In mineralizing cultures, the average velocity of Dmp1-Cre/tdTomato-positive cells was significantly reduced (0.7 µm/h), with many immobilized in the mineralizing nodule. Three apparent mechanisms for embedding of Dmp1-Cre/tdTomato-positive cells were observed. In some cases, a previously motile Dmp1-Cre/tdTomato-positive cell became immobilized in collagen fibril networks that were newly assembled around the cell, thereby entrapping it. In other cases, a motile Dmp1-Cre/tdTomato-positive cell moved into an already formed “collagen lacuna”, arrested its motility and became embedded. Alternatively, some cells switched on tdTomato expression in situ within a lacuna. These data provide new insight into the dynamic process of bone collagen assembly and suggest multiple mechanisms for osteocyte entrapment in collagen matrix.